Optimization of power system operation and development under emission trading scheme : : doctoral thesis - Pašičko, Robert (R. Pašičko ; Fakultet elektrotehnike i računarstva, 2014)
SUMMARY: Power system planning and development face new pressing challenges from climate change including the need to reduce its GHG emissions (climate change mitigation through different mechanisms such as emission trading, transition to low emission power system); and the need to adapt to climate change (climate change adaptation and vulnerability). Also, the development of energy sector should take the responsibility for the sustainable development – delivering positive and measurable impact on society, economy and environment. The main objective of the research was to develop and verify methodology and models for the assessment of emission trading and climate change impacts on sustainable power system development. Two models were designed to fit the proposed methodology. The first model is for the assessment of emission trading and fuel price impacts on long term marginal costs for different power plants. The second designed model enables measuring sustainable development indicators from generation capacity expansion. This developed algorithm enables the power system model to include emission price in power system operation and planning. Data from Croatian power system are used for the verification of proposed methodology, designed models and algorithm,. Verification steps are included: power system modeling, modeling sustainable development indicators and assessment of climate change impacts on power system planning. Finally, the integrative model based on proposed methodology, developed models and algorithm performed a wide set of modeled scenarios. This holistic approach of modeling emission trading and climate change impacts on long-term power system planning is verified by using data for Croatian power system until 2030. Results from verification of the proposed modeling are presented and discussed. Based on these results, a summary of main findings, recommendations for policy makers and energy planners, and area for further research in this field are proposed. -